In the "Stranger People's" country - Craddock, Charles Egbert, 1850-1922 (University of Nebraska Press, 2005)
"In the "Stranger People's" Country tells the story of contact between a late-nineteenth-century Tennessee mountain community and an amateur archaeologist who wants to open the graves of the prehistoric "leetle stranger people," a source of myth to the mountaineers. A politician looking for votes in the country has invited the archaeologist Shattuck to travel into the mountains with him, but a mountain woman, Adelaide Yates, threatens to shoot anyone who attempts to violate the graves. The courageous mountaineer Felix Guthrie joins the defense of the "stranger people" and competes with Shattuck for the attention of another mountain woman, Letitia Pettingill." "Author Mary Noailles Murfree (1850-1922) uses dialect and vivid descriptions of mountain scenes to introduce the reader to Appalachia and its people. She creates respectful representations of Appalachian life and explores some of the changes the arrival of outsiders brought to the mountains. Murfree's depiction of social and aesthetic issues increases our understanding of the nineteenth century and serves as a literary precursor of the twentieth-century Appalachian activist movements to preserve the environment against the strip-mining and chemical industries." "This edition of Murfree's 1891 novel, reprinted for the first time, includes notes about Appalachian dialect and the novel's references to archaeology, which have some basis in actual archaeological discoveries in Tennessee."--Jacket.
Original ed., published in 1891, written under Mary Noailles Murfree's pseudonym of Charles Egbert Craddock.
Keywords: Appalachian Region, Southern -- Fiction.; Archaeologists -- Fiction.; Mountain life -- Fiction.; Politicians -- Fiction.; Cemeteries -- Fiction.; Appalaches (Sud) -- Romans, nouvelles, etc.; Archéologues -- Romans, nouvelles, etc.; Vie en montagne -- Romans, nouvelles, etc.; Politiciens -- Romans, nouvelles, etc.; Cimetières -- Romans, nouvelles, etc.; Archaeologists; Cemeteries; Mountain life; Politicians; Southern Appalachian Region; American Literature.; English.; Languages & Literatures.; Fiction; Political fiction; Psychological fiction; Psychological fiction.; Political fiction.